Premna integrifolia ameliorates cyclophosphamide-induced hepatotoxicity by modulation of oxidative stress and apoptosis - Singh C.; Prakash C.; Tiwari K.N.; Mishra S.K.; Kumar V. (My University, 2025)
The present study was designed to evaluate the ameliorative effect of ethyl acetate extract of Premna integrifolia L. (EAEPI) leaves in cyclophosphamide (CP)-induced hepatic injury in mice. Mice were intoxicated with CP (200 mg/kg b. wt., i.p.) for 5 weeks or EAEPI (400 and 600 mg/kg b. wt., orally) in combination with CP. The results demonstrated that EAEPI exerts protective effect against CP induced hepatotoxicity, as evident from restoration of altered haematological parameters and alleviations of liver marker enzymes in serum. EAEPI also attenuated oxidative stress and antioxidant markers as evident from reversal of lipid peroxidation, glutathione levels as well as activities of catalase and superoxide dismutase enzymes. Moreover, EAEPI attenuated apoptosis and histopathological liver tissue damage in CP-intoxicated mice. In conclusion, EAEPI could protect mice liver against cyclophosphamide toxicity by inhibiting oxidative stress and apoptosis.The protective activity of EAEPI may be due to presence of polyphenolic compounds as identified by UHPLC–Q-TOF-MS/MS. © 2018 Elsevier Masson SAS